STRATEGI KOMUNIKASI RADIO KOMUNITAS USUKOM FM DALAM MEMPERTAHANKAN EKSISTENSINYA - Corry Novrica AP Sinaga (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2017)
This research is based on important and its strategic radio community university campus in north sumatra, specialized in field broadcasting , so for is important to increase strategy management in this world broadcasting radio community .Radio community is mass media that move in broadcast , formed by a group of people and used for the masyakat also, hence if a radio slowly have lost its existence in the eyes of the community, who to be the case is a threat ke-matia-an in penyiarannya, this needs to an increase in the quality of management broadcasting according to recitation needs for a community. Type used in this research was a sort of descriptive set qualitative , by adopting of observation, interviews and documentation.  The findings of this research is, that strategy communication and management a broadcast that is carried usukom fm less spoke in terms of his application, because less than maximum in the implementation of the management broadcasting. Maintain existensi a broadcast via the command of the broadcast schedule announcer as well as opened interaction directly and indirectly, as is the case to open a request through sms, telephon and served promotion for student activities campus on demand they. Keywords: the communications strategy , radio community , existence